A Novel training-based MIMO channel estimation scheme for layered space-time systems in frequency selective wireless channels - Siyau, Ming F. (Department of Aerospace, Power & Sensors, 2009)
New development in wireless technology using multiple antennas with appropriate space-time processing has recently become the new frontier of wireless communication systems due to the potential for providing very high spectral efficiency and enormous capacity improvement over the conventional wireless radio communications. The technical advances in using the multiple-input multiple-output (MIMO) wireless links present a promising breakthrough in resolving the bottleneck of current capacity limitation for future intensive wireless networks. The MIMO wireless systems utilize multiple antennas at both side of the transmitter and the receiver for enormous gains in spectral efficiency as well as system capacity in terms of higher data throughput by exploiting the multipath diversity in a rich scattering environment. A number of MIMO systems have been proposed to permit very high transmission rate, far exceeding the conventional communication technique. In particular, the Bell Laboratories layered space-time (BLAST) architecture has been presented that uses concept of spatial diversity and successive interference cancellation technique to improve the quality of signal reception over the flat-fading or the frequency selective fading channel. However, in order to achieve the quoted capacity gains in MIMO systems, the channeli nformation in terms of the multiple channeli mpulse responses(C IRs) and their fading coefficients must be known or estimated, which requires the design of a suitable channele stimator.T hus far, existing MIMO channele stimations chemesh aveb eenm ostly limited to the flat-fading case or cater specifically for coded space-time systems such as space-timeb lock code systems.I n this thesis,t he work is to considert he existing MIMO channel estimation techniques (used in the flat fading condition) and extend them to cater for a more realistic time-varying, frequency selective fading channel. The focus of this thesis has been the design and development of suitable training-based MIMO channel estimation scheme as well as the formulation of a new pilot code to enable effective estimation for the frequency selective channel. The novel channel estimator is also incorporatedi nto the BLAST architecturet o allow the practical assessmenotf using nonidealized channel to be studied and analysed for the performance of the MIMO systems. The driver for this work has been the recognition of the importance of channel knowledge for all the MIMO system to be used in practical application.